Accessibility in a higher education institution in Tocantins: case report (Research, Society and Development, 2021)
This article aimed to verify the inclusion process of a Higher Education Institution (HEI) in Tocantins. Initially, a brief context on inclusive education was elaborated, as this idea arose from the need to know what is being done in the area of special education in a higher education institution in Tocantins. Subsequently, a survey with a qualitative focus was carried out with the students and employees of the IES who work directly with these students, and from the data that were collected, it was possible to measure the quality of services offered by the IES, which currently has 42 academics with special educational needs. It is noteworthy that the HEI used in the research is one of the largest institutions in the state, with approximately 6 thousand students. Finally, improvements were suggested for adaptations and possible potential to be achieved by special academics and all those involved in the teaching-learning process at the IES. The HEI used in this report provides the necessary subsidies to make the inclusion process viable.